Social Media Management: A complete guide - Hart, Marcus (New York Murphy and Moore, 2023)
Social media refers to a set of computer-mediated interactive technologies that allow the sharing and creation of ideas, information and other forms of expression, with the aid of social networks and virtual communities. Social media services are interactive Web 2.0 applications that use Internet technology. The social network revolution led to the emergence of networking sites. Some popular social networking sites include Facebook, Twitter, Instagram, Snapchat, etc. Modern youth spend a major share of their time on social networks. This is due to the widespread use of smartphones.
Keywords: Social Media; Media management; Media Awareness